Role of Judicial Review in Shaping Public Policy and Ensuring Accountability - Shamaila Khalid; Tabinda Mehdi; Rizwana Zaman; Sher Hassan (Social Science Review Archives, 2025)
Courts use judicial review to ensure that laws and government actions are constitutional, lawful and respectful of individuals’ rights. The paper analyzes judicial review as an essential element in controlling how public policies develop and ensuring the government remains within its legal boundaries. Judicial review controls the make-up of laws and government actions. Jurists provide clarity on the legal meaning in decisions which later influence how legislation is understood. Judges determine whether laws and actions uphold constitutional guarantees, comply with international human rights principles and are just. The impact of judicial review on progressing environmental regulations, education, healthcare, rights of minorities and enhancing transparency in public administration is explored in this paper. The paper shows, supported by relevant case studies, that judicial review helps safeguard the principles of the rule of law and prevents the misuse of authority by both the legislature and executive. The paper explores how clashes occur when deciding between judicial activism and judicial restraint. Extensive judicial interference can be regarded as an encroachment on democratic processes if such action contradicts the framework set by the constitution. Thus, the paper argues that careful, value-driven judicial action should be adopted to guard democratic mechanisms while allowing people’s elected officials to exercise appropriate functions within the law. The authors argue that judicial review plays an essential role in securing the constitution and maintaining principles like accountability, transparency and inclusive democracy. A trustworthy judiciary plays a vital role in maintaining the integrity of democracy and ensuring people’s faith in their elected leaders.